Estilos de aprendizaje y rendimiento académico de estudiantes de 2° de secundaria en educación para el trabajo de una institución educativa del Callao - Jara Quispe, Gladys Rosalía (2010)
This research aims to establish the relationship between learning styles and academic performance of students in high school 2º Work Education for an Educational Institution of Callao. The research design was descriptive correlational. The sample was 69 students, the afternoon shift, ages 12 to 16 years. The instrument used was the Questionnaire of Honey - Alonso of Learning Styles (CHAEA), and the academic performance of Pupils Assessment Record 2009 in the area of Education for Work (EPT), was used SPSS version 15.0, as the statistical parametric r of Pearson where This result is statistically significant correlation exists with reflective learning style to a level of 0.01 with r = 400 ** with academic performance, there is also correlation with the theoretical style to academic performance but at a level of 0.05 with r = 244 *, thereby approving the Hypothesis 2 and Hypothesis 3, while in the active style as pragmatic style did not correlate with academic performance.